Fast‐track versus long‐term hospitalizations for patients with non‐disabling acute ischaemic stroke. (3rd September 2018) - Fladt, J.; Hofmann, L.; Coslovsky, M.; Imhof, A.; Seiffge, D. J.; Polymeris, A.; Thilemann, S.; Traenka, C.; Sutter, R.; Schaer, B.; Kaufmann, B. A.; Peters, N.; et al.
Abstract : Background and purpose: The aim was to assess the feasibility and safety of fast‐track hospitalizations in a selected cohort of patients with stroke. Methods: Patients hospitalized at the Stroke Center of the University Hospital Basel, Switzerland, with an acute ischaemic stroke confirmed on magnetic resonance diffusion‐weighted imaging were included. Neurological deficits of the included patients were non‐disabling, i.e. not interfering with activities of daily living and compatible with a direct discharge home. Patients with premorbid disability were excluded. All patients were admitted to the Stroke Center for ≥24 h. Two study groups were compared – fast‐track hospitalizations (≤72 h) and long‐term hospitalizations (>72 h). The primary end‐point was a composite of any unplanned rehospitalization for any reason within 3 months since hospital discharge and a modified Rankin Scale 3–6 at 3 months. Adjustment for confounders was done using the inverse probability of treatment weights (IPTW). Results: Amongst the 521 patients who met the inclusion criteria, fast‐track hospitalizations were performed in 79 patients (15%). In the fast‐track group, seven patients (8.9%) met the primary end‐point, compared to 37 (8.4%) in the long‐term group [odds ratio (OR) 1.06, 95% confidence interval (CI) 0.42–2.34, P = 0.88]. After weighting for IPTW, the odds of the primary end‐point remained similar between the two arms (ORIPTW 1.27, 95% CI 0.51–3.16, P = 0.61). The costs of fast‐track hospitalizations were lower, on average, by 4994. Conclusions: Fast‐track hospitalizations including a full workup proved to be feasible, showed no increased risk and were less expensive than long‐term hospitalizations.